Protein Aeromonas Hydrophila Sebagai Vaksin untuk Pengendalian Mas (Motile Aeromonas Septicemia) pada Jambal Siam (Pangasius hypophthalamus) - Olga Olga; Ririen Kartika Rini; Junius Akbar; Alim Isnansetyo; Langkah Sembiring (Jurnal Perikanan Universitas Gadjah Mada, 2007)
Objectives of this study were to find out the protein of Aeromonas hydrophila for vaccine, and to evaluate the efficacy of the protein to control Motile Aeromonas Septicemia (MAS) in catfish (Pangasius hypophthalamus). A. hydrophila was isolated from the kidney of diseased catfish. The isolate was cultured, sonicated and sentrifuged into cell-free extract and debris. The protein in the cell-free extract was precipitated with ammonium sulphate, dialized, then fractionated by gel filtration column chromatography on Sephadex G150.The concentration of protein were estimated by spectrophotometer at 280 nm. Fractions obtained from the gel filtration with high concentration of protein were analized by sodium dodocyl sulphate-polyachrylamide gel electrophoresis (SDS-PAGE). The protein bands obtained from SDS-PAGE with molecular weight more than 10 kDa were tested for immunogenicity to mice. Futhermore, the most immunogenic protein was used for fish vaccination. The vaccinated and unvaccinated fishes were chalenged with A. hydrophila.The results indicated that vaccination with the protein significantly increased (P<0.01) the antibody titer either in mice or catfish. Relative Percent Survival of catfish vaccinated with the protein at 5; 7.5; and 10 µg/fish were 61.54%, 80.77% and 76.92%, respectively. The optimum dose of vaccine was 8.33 µg/fish with maximum RPS of 82.05%.